Istanbul election: Remaking of Turkey's new political landscape? - Galip Dalay (Stiftung Wissenschaft und Politik (SWP), 2019)
Istanbul's fiercely fought municipal election is over. The opposition candidate, Ekrem İmamoğlu, won a landslide victory over his rival. The governing Justice and Development Party (AK Party) has arguably suffered its most severe defeat since coming to power in 2002. The repercussions and reverberations of this election will be deeply felt across the political spectrum in Turkey. This election will have a formative impact on this new period of Turkish politics. Turkey has gained new political actors, for example İmamoğlu, as a result of this election. The same election has also further opened the way for contestations on the conservative end of the political spectrum. Former President Abdullah Gül, former Prime Minister Ahmet Davutoğlu, and former Minister of Economy Ali Babacan are set to break away from the AK Party and form their own political movements.
Keywords: 320